2021
DOI: 10.2169/internalmedicine.6077-20
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant Therapy for Frail Patients with Atrial Fibrillation

Abstract: The prevalence of atrial fibrillation (AF) increases with age, as does the proportion of patients with frailty. AF patients with frailty have a higher risk of stroke than those without frailty, and progressive frailty caused by stroke is also associated with a worse prognosis. Despite this, anticoagulant therapy tends to not be used in frail patients because of the risk of falls and bleeding complications. However, some studies have shown that anticoagulant therapy improves the prognosis in patients with frail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Frail patients with atrial fibrillation have higher risks of incidental stroke, mortality and duration of hospitalisation than non-frail ones [ 35 ] and anticoagulants can improve the prognosis of frail individuals. Despite this, the prescription of anticoagulants is usually restricted in frail patients due to the risk of falls and bleeding complications [ 36 ]. A meta-analysis by Oqab et al comprising three studies on the prescription of anticoagulants in older adults with atrial fibrillation, concluded that frail patients were less likely to receive this medication when compared with non-frail ones [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Frail patients with atrial fibrillation have higher risks of incidental stroke, mortality and duration of hospitalisation than non-frail ones [ 35 ] and anticoagulants can improve the prognosis of frail individuals. Despite this, the prescription of anticoagulants is usually restricted in frail patients due to the risk of falls and bleeding complications [ 36 ]. A meta-analysis by Oqab et al comprising three studies on the prescription of anticoagulants in older adults with atrial fibrillation, concluded that frail patients were less likely to receive this medication when compared with non-frail ones [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulant therapy is an important topic in geriatric medicine, introducing the importance of clinical-decision making tools [ 31 ]. In literature, the main reasons reported to refrain from the prescription of oral anticoagulant therapy in older people include age itself, current concomitant antiplatelet therapy, an increased risk of bleeding or risk of falls, cognitive impairment, functional impairment or difficulty in maintaining adequate INR values [ 32 ]. By contrast, given the lack of specific recommendations, the potential opposite risk is the prescription of such drugs only based on stroke risk scores and not accounting frailty condition of older adults with AF [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The other component of the worsened outcomes in some of the lowest tertile groups was that these individuals were less likely to be prescribed indicated antithrombotic therapy. It is plausible that this prescribing reticence reflects concerns about antithrombotic therapy in the frail population 7 . This includes worries about falls risk and bleeding complications in more frail individuals.…”
Section: Anthropometric Parameters and Af Outcomes: A Path To Precisi...mentioning
confidence: 99%